2013
DOI: 10.3182/20131216-3-in-2044.00060
|View full text |Cite
|
Sign up to set email alerts
|

Application of Uncertainty and Sensitivity Analysis to a Kinetic Model for Enzymatic Biodiesel Production

Abstract: This paper demonstrates the added benefits of using uncertainty and sensitivity analysis in the kinetics of enzymatic biodiesel production. For this study, a kinetic model by Fedosov and co-workers is used. For the uncertainty analysis the Monte Carlo procedure was used to statistically quantify the variability in the model outputs due to uncertainties in the parameter estimates; showing the model is most reliable in the start (first 5 hours) of the reaction. To understand which input parameters are responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Samukawa and co-workers found that they can increase the reuse of the immobilised enzyme (a clear indication of a reduction in enzyme deactivation), by using a stepwise feeding strategy. This kept the methanol content in the reactor below the concentration that gave the highest initial rate of FAME production (Samukawa et al 2000). Hence we wished to extend their work by actually being able to maintain the concentration of methanol in the reactor ({CH critical }) that gave the best initial rate, at each time increment t i , by minimizing the objective function in (4).…”
Section: Methanol Feeding Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Samukawa and co-workers found that they can increase the reuse of the immobilised enzyme (a clear indication of a reduction in enzyme deactivation), by using a stepwise feeding strategy. This kept the methanol content in the reactor below the concentration that gave the highest initial rate of FAME production (Samukawa et al 2000). Hence we wished to extend their work by actually being able to maintain the concentration of methanol in the reactor ({CH critical }) that gave the best initial rate, at each time increment t i , by minimizing the objective function in (4).…”
Section: Methanol Feeding Optimizationmentioning
confidence: 99%
“…As in our previous work (Price et al 2013), the Monte Carlo method was used to propagate the uncertainty of the kinetic parameters on the output (prediction) uncertainty of the model (Sin et al 2009). The confidence intervals from the parameter fitting is used to specify the input uncertainty in the parameter estimates and Latin hypercube sampling with correlation control is used for sampling of the parameters in the sample parameter space (Helton and Davis 2003).…”
Section: Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The sample number was set at 1,000 (chosen for consistency with past studies; this was sufficient to obtain a good sampling rate whilst not overloading computing resources). For more information on the use of uncertainty and sensitivity analysis in process modelling please see the following references (76,77).…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Nevertheless, these methods have turned out to be useful tools, sometimes resulting in fast solutions and they are already implemented in functions (e.g., in Matlab or R), which are easy to apply. They can be combined with statistical methods like Monte Carlo (MC) simulation, sensitivity, uncertainty, and/or identifiability analysis, in order simulate output uncertainty and to gain more information of the process (Hines, ; Price, Nordblad, Woodley, & Huusom, ; Raue et al, ; Sin et al, ).…”
Section: Introductionmentioning
confidence: 99%